Automated scoring of dicentric chromosomes differentiates increased radiation sensitivity of young children after low dose CT exposure in vitro. (2nd November 2018) - Oestreicher, Ursula; Endesfelder, David; Gomolka, Maria; Kesminiene, Ausrele; Lang, Peter; Lindholm, Carita; Rößler, Ute; Samaga, Daniel; Kulka, Ulrike
Abstract: Purpose: Automated detection of dicentric chromosomes from a large number of cells was applied to study age-dependent radiosensitivity after in vitro CT exposure of blood from healthy donors. Materials and methods: Blood samples from newborns, children (2–5 years) and adults (20–50 years) were exposed in vitro to 0 mGy, 41 mGy and 978 mGy using a CT equipment. In this study, automated scoring based on 13, 000–31, 000 cells/dose point/age group was performed. Results for control and low dose points were validated by manually counting about 26, 000 cells/dose point/age group. Results: For all age groups, the high number of analyzed cells enabled the detection of a significant increase in the frequency of radiation induced dicentric chromosomes in cells exposed to 41 mGy as compared to control cells. Moreover, differences between the age groups could be resolved for the low dose: young donors showed significantly increased risk for induced dicentrics at 41 mGy compared to adults. Conclusions: The results very clearly demonstrate that the automated dicentric scoring method is capable of discerning radiation induced biomarkers in the low dose range (<100 mGy) and thus may open possibilities for large-scale molecular epidemiology studies in radiation protection.